The Idea of a Greater Croatia and Genocide as an Instrument for its Realization - Krestić, Vasilije (Napredak, 2022)
The paper consists of two selected chapters from the author’s monograph published under the title Through Genocide to a Greater Croatia. The text points to the development of the great state idea among the Croats, aimed at creating the ethnically pure and Catholic state of Croatia, which is followed from the middle of the 19th century to modern times. The genocide over the Serbian people perpetrated in the so-called “Independent State of Croatia” from 1941 to 1945 was also guided by that idea. The idea was continued during Tuđman’s coming to power in 1990, and one of the first moves of the new government was to change Croatia’s Constitution by turning the Serbs in Croatia as a constitutional nation into a national minority.
Keywords: Croatia; genocide over Serbs; continuity of the Greater Croatia state project